Characterization data of reference cement CEM I 42.5 R used for priority program DFG SPP 2005 “Opus Fluidum Futurum – Rheology of reactive, multiscale, multiphase construction materials” - Lu, Z. C.; Haist, M.; Ivanov, D.; Jakob, Cordula; Jansen, Daniel; Leinitz, S.; Link, J.; Mechtcherine, V.; Neubauer, Jürgen; Plank, J.; Schmidt, W.; Schilde, C.; et al. (Data in Brief, 2019)
A thorough characterization of starting materials is the precondition for further research, especially for cement, which contains various phases and presents quite a complex material for fundamental scientific investigation. In the paper at hand, the characterization data of the reference cement CEM I 42.5 R used within the priority program 2005 of the German Research Foundation (DFG SPP 2005) are presented from the aspects of chemical and mineralogical compositions as well as physical and chemical properties. The data were collected based on tests conducted by nine research groups involved in this cooperative program. For all data received, the mean values and the corresponding errors were calculated. The results shall be used for the ongoing research within the priority program.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Characterization; DFG SPP 2005; Portland cement